(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2024)
This study examines the portrayal of existential crises in Western and non-Western literature through the analysis of The Catcher in the Rye by J.D. Salinger and The God of Small Things by Arundhati Roy. While much research has explored existential themes in Western literature, there is a gap in the comparative analysis of how these themes are depicted across different cultural contexts. Using Existentialist theory as the methodological framework, the study analyzes the internal struggles of characters, focusing on themes such as alienation, identity, and meaning. The findings reveal that while both texts explore existential angst, cultural differences shape the characters’ responses to these crises. Western literature emphasizes individualism, while non-Western perspectives are more deeply influenced by social and familial constraints. The study recommends further research into cross-cultural representations of existentialism in adolescent literature and suggests the therapeutic potential of literature in addressing existential crises.